Functional Significance of GnRH and Kisspeptin, and Their Cognate Receptors in Teleost Reproduction - GOPURAPPILLY, RENJITHA; Ogawa, Satoshi; Parhar, Ishwar S. (Frontiers in Endocrinology, 2013)
Guanine nucleotide binding protein (G-protein)-coupled receptors (GPCRs) are eukaryotic transmembrane proteins found in all living organisms. Their versatility and roles in several physiological processes make them the single largest family of drug targets. Comparative genomic studies using various model organisms have provided useful information about target receptors. The similarity of the genetic makeup of teleosts to that of humans and other vertebrates aligns with the study of GPCRs. Gonadotropin-releasing hormone (GnRH) represents a critical step in the reproductive process through its cognate GnRH receptors (GnRHRs). Kisspeptin (Kiss1) and its cognate GPCR, GPR54 (=kisspeptin receptor, Kiss-R), have recently been identified as a critical signalling system in the control of reproduction. The Kiss1/GPR54 system regulates GnRH release, which is vital to pubertal development and vertebrate reproduction. This review highlights the physiological role of kisspeptin-Kiss-R signalling in the reproductive neuroendocrine axis in teleosts through the modulation of GnRH release. Moreover, we also review the recent developments in GnRHR and Kiss-R with respect to their structural variants, signalling mechanisms, ligand interactions and functional significance. Finally, we discuss the recent progress in identifying many teleost GnRH-GnRHR and kisspeptin-Kiss-R systems and will consider their physiological significance in the control of reproduction.